2019
DOI: 10.1038/s41598-019-41092-6
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of newly synthesized platinum nanoparticles with ICR-191 and their potential application

Abstract: One of the greatest challenges of modern medicine is to find cheaper and easier ways to produce transporters for biologically active substances, which will provide selective and efficient drug delivery to the target cells, while causing low toxicity towards healthy cells. Currently, metal-based nanoparticles are considered a successful and viable solution to this problem. In this work, we propose the use of novel synthesis method of platinum nanoparticles (PtNPs) connected with their precise biophysical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Increasing the ICR-191 concentration corresponded to decreasing cellular metabolic activity in non-cancerous HaCaT and cancerous MelJuSo cells incubated with PtNPs. In addition, ICR-191 has a more powerful impact on HaCaT than on MelJuSo cells [40]. PtNPs were established as having anticancer and cytotoxic activities against various type of cancerous and non-cancerous cells ha.…”
Section: Effects Of Ptnps On Cell Viability and Proliferation Of Thp-mentioning
confidence: 99%
“…Increasing the ICR-191 concentration corresponded to decreasing cellular metabolic activity in non-cancerous HaCaT and cancerous MelJuSo cells incubated with PtNPs. In addition, ICR-191 has a more powerful impact on HaCaT than on MelJuSo cells [40]. PtNPs were established as having anticancer and cytotoxic activities against various type of cancerous and non-cancerous cells ha.…”
Section: Effects Of Ptnps On Cell Viability and Proliferation Of Thp-mentioning
confidence: 99%
“…52 Several studies have found that PtNPs of 50 nm have an anticancer effect, however other studies showed that PtNPs of 5 nm and 20 nm had no anticancer effect. 10,21,50,53,54 Therefore, in the present study, platinum nanoparticles were synthesized by chemical reduction following the methodology of Shim et al, to achieve a size of 50 nm. 50 The size, shape, and crystallinity of the PtNPs were determined by TEM and X-ray diffraction (XRD).…”
Section: Evaluation Of Platinum Nanoparticlesmentioning
confidence: 99%
“…[ 5,12–17 ] However, exposure of PtNPs in a biological system might be associated with unanticipated hazards. [ 18–20 ] There are numerous reports on nephrotoxicity, hepatotoxicity, and inflammatory responses along with DNA damage induced by Pt‐based NPs. [ 21,22 ] On the other hand, PtNPs are also reported to inhibit pulmonary inflammation by exerting antioxidants and free radical scavenging activity.…”
Section: Introductionmentioning
confidence: 99%